Impact of Macroeconomic Indicators: Economic Growth, Inflation, Interest Rates and Exchange Rates on the Condition of Foreign Direct Invesment (FDI) in Indonesia 2000-2019 - Teddy Christianto Leasiwa; Hermi Oppier; Desry Jonelda Louhenapessy; Abdul Muis Kaimuddin (Budapest International Research and Critics University, 2022)
Study this aim for knowing influence growth economy, inflation, Interest Rate, and value exchange rate to FDI investment in Indonesia. Data used in study this is secondary data sourced _ from World Bank Data and Bank Indonesia. Data analysis techniques in study this is analysis regression multiple. Research results showing that Economic Growth and Exchange Rates have an effect positive but no significant to FDI investment, while Inflation and Interest Rates have a negative and significant effect to FDI investment in Indonesia. From result research, can seen that ethnic group flower is the most influential factor strong to FDI investment in Indonesia. In this case, the government should pay more attention to interest rates in order to attract investors to invest.